2010
DOI: 10.1007/s10157-010-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

Progression of cyclophosphamide-induced acute renal metabolic damage in carnitine-depleted rat model

Abstract: Oxidative stress is not involved in CP-induced renal injury in this model. Carnitine deficiency and energy starvation constitute risk factors in and should be viewed as a mechanism during CP-induced nephrotoxicity. PLC prevents development of CP-induced nephrotoxicity by increasing intracellular carnitine content, intramitochondrial CoA-SH/acetyl-CoA ratio and energy production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…Carnitine deficiency and energy starvation have been reported to play critical role in chemical-induced nephrotoxicity (Sayed-Ahmed, 2010). In contrast, acylcarnitines and particularly propionyl-L-carnitine, which is a product of the enzymatic esterification of carnitine (Murphy et al, 2012), have been described to prevent the development of renal failure by increasing intracellular carnitine levels and energy production (Sayed-Ahmed, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine deficiency and energy starvation have been reported to play critical role in chemical-induced nephrotoxicity (Sayed-Ahmed, 2010). In contrast, acylcarnitines and particularly propionyl-L-carnitine, which is a product of the enzymatic esterification of carnitine (Murphy et al, 2012), have been described to prevent the development of renal failure by increasing intracellular carnitine levels and energy production (Sayed-Ahmed, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with potential nephrotoxicity were given to these patients before (cyclophosphamide) (32, 33) or after transplantation (cyclosporine or tacrolimus). CNIs cause renal failure by vascular toxicity, leading to vasoconstriction and tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of CP has been reported to increase malondialdehyde (MDA), decrease in reduced glutathione (GSH), and decrease the activities of kidney's antioxidative enzymes, such as superoxide dismutase, glutathione peroxidase (GPx), glutathione reductase, and catalase. [7][8][9][10] There is growing evidence for the role of aminoguanidine (AG) as an antioxidant. Many studies have demonstrated that AG acts as an antioxidant, and prevents the loss of antioxidant enzyme activities as well as cellular damage.…”
Section: Introductionmentioning
confidence: 99%